Schizophrenia and catatonia: from ICD-10 to ICD-11 - Nickl-Jockschat, Thomas; Steiner, Johann; Hirjak, Dusan; Hasan, Alkomiet (Der Nervenarzt, 2025)
The classification of psychotic disorders has undergone a variety of changes. Since Karl Ludwig Kahlbaum’s (Kahlbaum 1874) first descriptions of catatonic states and Emil Kraepelin’s (Kraepelin 1883) nosological classification of psychotic syndromes in the second half of the nineteenth century, the diagnostic criteria for these disorders have been repeatedly modified, significantly impacting clinical practice. Eugen Bleuler (Bleuler 1911) coined the term “schizophrenia”, emphasizing the disturbances in thinking, feeling and acting that he had observed. With the introduction of the 11th version of the International Classification of Diseases (ICD-11), several significant changes to the diagnostic criteria were introduced. First-line symptoms according to Schneider lost importance. The subtypes (e.g., paranoid, hebephrenic and catatonic schizophrenia) were also omitted and symptom and progression classifiers have been introduced instead. Finally, catatonia is now defined as an independent diagnostic entity, while in ICD-10 it was still assigned to schizophrenia under the code F20.2. This recognizes catatonia’s independent, cross-diagnostic nature. Due to these symptom and progression classifiers, the ICD-11 now takes a more a hybrid categorical and dimensional approach to the diagnosis than the previous version.
Gesehen am 28.10.2025